Soil Organic Carbon Development and Turnover in Natural and Disturbed Salt Marsh Environments. Issue 2 (19th January 2021) - Luk, Sheron Y.; Todd‐Brown, Katherine; Eagle, Meagan; McNichol, Ann P.; Sanderman, Jonathan; Gosselin, Kelsey; Spivak, Amanda C.
Abstract: Salt marsh survival with sea‐level rise (SLR) increasingly relies on soil organic carbon (SOC) accumulation and preservation. Using a novel combination of geochemical approaches, we characterized fine SOC (≤1 mm) supporting marsh elevation maintenance. Overlaying thermal reactivity, source (δ 13 C), and age (F 14 C) information demonstrates several processes contributing to soil development: marsh grass production, redeposition of eroded material, and microbial reworking. Redeposition of old carbon, likely from creekbanks, represented ∼9%–17% of shallow SOC (≤26 cm). Soils stored marsh grass‐derived compounds with a range of reactivities that were reworked over centuries‐to‐millennia. Decomposition decreases SOC thermal reactivity throughout the soil column while the decades‐long disturbance of ponding accelerated this shift in surface horizons. Empirically derived estimates of SOC turnover based on geochemical composition spanned a wide range (640–9, 951 years) and have the potential to inform predictions of marsh ecosystem evolution. Plain Language Summary: Salt marsh survival with rising sea levels increasingly depends on the accumulation and preservation of buried organic carbon. Marsh soil organic carbon development reflects at least three processes: burial of differently reactive compounds that derive from local grasses, redeposition of old carbon (9%–17%), and microbial reworking. Decomposition results in a progressive decrease in the thermal reactivity of soil organic carbon, and disturbances such as ponding can accelerate this shift. Modeled rates of geochemically defined soil organic carbon pools turnover on the order of centuries‐to‐millennia and can refine predictions of salt marsh sustainability. Key Points: Salt marsh soils preserved compounds with a range of reactivities that were derived from local grasses 9%–17% of surface soil carbon was old, likely reflecting redeposition of eroded creekbank material Decomposition decreases soil organic carbon thermal reactivity, and disturbances accelerate this shift, particularly in surface horizons